Impact of Exchange Rate Management on the Nigerian Economic Growth: Empirical Validation (American International Journal of Economics and Finance Research, 2019)
This paper examined the impact of Exchange Rate Management on economic growth in Nigeria between 1980 and 2015. The study was set to gauge how the management of exchange rate in Nigeria has impacted the economy. The study employed the Ordinary Least Square (OLS) method in its analysis. Co-integration and Error Correction Techniques were used to establish the Short-run and Long-run relationships between economic growth and other relevant economic indicators. The result revealed that exchange rate management proxy by various exchange rates regimes in Nigeria was not germane to economic growth. Rather, government expenditure, inflation rate, money supply and foreign direct investment significantly impact on economic growth in Nigeria. It is against this backdrop that the Nigerian economy must diversify her export base to create room for more inflow of foreign exchange.